2020
DOI: 10.1111/1750-3841.15180
|View full text |Cite
|
Sign up to set email alerts
|

Whole nuña bean (Phaseolus vulgaris L.) flour showed higher direct expansion during extrusion processing at relatively lower temperatures

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 43 publications
3
9
1
Order By: Relevance
“…It is important to note that different extrusion conditions, such as feeding rate, screw profile, die diameter, temperature, moisture content, all contribute to the range of extrusion characteristics of raw material because extrusion processing is a Multiple Input Multiple Output system (Eerikäinen et al., 1994; Ganjyal et al., 2006). By considering the SME values in these previously reported studies, the SME values at the highest ER of beans and peas were lower compared with SME values in our study (Gu et al., 2020; Pietrysiak et al., 2020). This could be the reason why their ER was lower than the ER of lentils in our study.…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…It is important to note that different extrusion conditions, such as feeding rate, screw profile, die diameter, temperature, moisture content, all contribute to the range of extrusion characteristics of raw material because extrusion processing is a Multiple Input Multiple Output system (Eerikäinen et al., 1994; Ganjyal et al., 2006). By considering the SME values in these previously reported studies, the SME values at the highest ER of beans and peas were lower compared with SME values in our study (Gu et al., 2020; Pietrysiak et al., 2020). This could be the reason why their ER was lower than the ER of lentils in our study.…”
Section: Resultscontrasting
confidence: 64%
“…Another study on the extrusion of the whole lentil showed that the highest ER (2.32) was achieved at feed moisture of 15%, a temperature of 150 °C, and a screw speed of 300 rpm; however, the screw profile was not provided (Ghumman, Kaur, Singh, et al., 2016). Interestingly, the Richlea lentil variety in this study had a greater range of ER (2.55 to 3.60) compared with the data from the literature on whole lentils (1.3 to 3.27), dry peas (2.70 to 3.34), and beans (1.41 to 3.03) (Ghumman, Kaur, Singh, et al., 2016; Gu et al., 2020; Pietrysiak et al., 2020; Rathod & Annapure, 2016). It is important to note that different extrusion conditions, such as feeding rate, screw profile, die diameter, temperature, moisture content, all contribute to the range of extrusion characteristics of raw material because extrusion processing is a Multiple Input Multiple Output system (Eerikäinen et al., 1994; Ganjyal et al., 2006).…”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…| 171 (Pietrysiak et al, 2020;Ragaee & Abdel-Aal, 2006). In this study, T g ranged from 70.5°C to 78.3°C for WI17-MV19 and WI19-UW20, respectively.…”
Section: Pasting Propertiesmentioning
confidence: 59%
“…Extrusion is a popular food processing technique in which material is simultaneously subjected to high temperature, mechanical energy, and pressure, and finally forced through a small opening (Gu et al., 2017; Li et al., 2017). Final product characteristics depend on the chemical composition of the raw material and the operating parameters, including screw speed, moisture content, barrel temperature, and die dimensions (Gu et al., 2017; Pietrysiak et al., 2020). The demand for extruded snacks is increasing due to their convenient characteristics of consumption, preparation, and storage (Brennan et al., 2013).…”
Section: Introductionmentioning
confidence: 99%